A Bibliometric Review on Dynamic Capability - Yudistira, Yudi; Arkeman , Yandra; Andati, Trias; Jahroh , Siti (Indonesian Journal of Business and Entrepreneurship, 2022)
Dynamic capability is an organization’s ability to integrate, build, and rearrange its internal and external competencies to face the rapidly changing environment. The objectives of dynamic capabilities consist of (1) the capacity to sense and form opportunities and threats (sensing); (2) capacity to seize existing opportunities (seizing); and (3) the capacity to maintain competitiveness through upgrading, merging, protecting, and reconfiguring business assets, both tangible and intangible. This study aims to determine the development of dynamic capability research trends published by leading Scopus-based journals. The data analyzed consisted of 1194 indexed research publications from 2012 until 2021. The data is then processed and analyzed using the VoS viewer application to determine the bibliometric map of dynamic capability research development. There are several definitions of dynamic capability and implications for the firm environment. Keywords: dynamic capability, bibliometric, Vos viewer, business environment, scientometric